Powłoki w Kształcie Walca Niekołowego (1) - Basuli, S. (Engineering Transactions, 1967)
Attempts have been made to find out the displacement components of a general Cylindrical shell under bending. Usual displacement equations involving axial, circumferential and normal displacements have been modified to form an eighth order Donnell type partial differential equation in normal displacement whereas the differential equations for axial and circumferential displacements are of fourth order each involving normal displacement only. Proposed solution assumes Levy type series solutions for the displacements. Numerical solutions are obtained for a shell whose radius of curvature varies exponentialy.